Development of Polyvoltine breed, APMG249 of Silkworm Bombyx Mori L. for Hybrid Preparation Suitable to Tropical Regions of India - Seshagiri, S. V.; Ramesha, C.; Prasad, Rajendra; Raju, P. J. (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2016)
Even after introduction of bivoltine hybrids to the field, the popularity of Poly x Bivoltine hybrids have not come down and 85% of the raw silk produced in our country is from cross breeds. Enrichment of silkworm breeds and synthesis of new gene combinations by conventional breeding technique is one of the important tools. The genetic constitution of the selected genotypes and non-genetic variability produced by the environmental factors are the two key factors while development of a breed. Keeping these, five polyvoltine breeds i.e. SDMW1CT, ROSY, GD, GP3 and GP2 maintained at Andhra Pradesh State Sericulture Research and Development Institute were selected as initial resource material. By utilizing these, a total of twenty new combinations were prepared and their performance was evaluated. Based on evaluation index and superiority of the new combinations, three new combinations were identified and accordingly three breeding plans were designed. In the present paper out of these breeding plans, the breeding plan which led to the development of polyvoltine breed, APMG249 is discussed. The breeding line was stabilized for their quantitative and qualitative traits by F10 generation and the performance was studied up to F12 generation. During breeding, inbreeding coupled with appropriate selection procedures were carried out and the resultant was named as ‘APMG249’. The newly developed polyvoltine breed was subjected for hybrid testing and field trials.